Effect of 'wheat Qu' on the fermentation processes and volatile flavour‐active compounds of Chinese rice wine (Huangjiu). Issue 1 (19th March 2013) - Chen, Shuang; Xu, Yan
Abstract : Wheat Qu is a unique saccharifying agent used for Chinese rice wine brewing. In recent years, the impact of wheat Qu on Chinese rice wine flavour has attracted great interest. In this study, Chinese rice wine fermentations were conducted with different saccharifying agents (wheat Qu and mixed commercial enzymes) to study the effect of wheat Qu on the fermentation process and aroma characteristics of Chinese rice wine. Our results showed that wheat Qu not only acted as a saccharifying agent, but also increased yeast activity and the formation of aroma compounds. A higher yeast growth and fermentation rate, in addition to a lower yeast death rate, were observed when wheat Qu was used as a saccharifying agent. Global analysis of the aromatic profiles revealed that the use of wheat Qu greatly promoted the formation of the aroma compounds during a Chinese rice wine fermentation. The concentrations of the volatile phenolic compounds and higher alcohols were higher in the Chinese rice wine samples fermented with wheat Qu. It was concluded that the role of wheat Qu cannot simply be replaced by commercial enzymes and that the Chinese rice wine aromatic profiles can be modulated depending on the amount of wheat Qu used in the fermentation. Copyright © 2013 The Institute of Brewing & Distilling